2002
DOI: 10.1002/1439-7641(20020215)3:2<209::aid-cphc209>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Surface Structure of Untreated Parallel and Fishbone Carbon Nanofibres: An Infrared Study

Abstract: Parallel and fishbone carbon nanofibres have an interesting and varied surface. Although HRTEM (see image) shows some detail, the characterisation provided by infrared spectroscopy reveals a wealth of defect‐rich structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…3) shows that the fibers are indeed of the fishbone type, however, with irregularities in the graphene sheets. The distance between the graphene sheets is about 3.4 Å , a value which corresponds well with values that were obtained with XRD and to that reported by other authors [3,8,35]. The core in CNF a.s. is either empty, or filled by an amorphous carbon phase or highly disordered graphene sheets.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…3) shows that the fibers are indeed of the fishbone type, however, with irregularities in the graphene sheets. The distance between the graphene sheets is about 3.4 Å , a value which corresponds well with values that were obtained with XRD and to that reported by other authors [3,8,35]. The core in CNF a.s. is either empty, or filled by an amorphous carbon phase or highly disordered graphene sheets.…”
Section: Resultssupporting
confidence: 90%
“…The macroscopic CNF bodies consist of skeins of interwoven fibers [1,3,7]. The core of the individual fibers most probably consist of highly disordered graphene sheets or an amorphous carbon phase which is removed upon HNO 3 treatment [1,8]. Only recently, it has been shown that it is also possible to grow in a single-step fishbonetype CNF with a hollow core throughout the length of the fiber [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Figures 5 and 6 show the infrared spectra for the oxidation of parallel fibres in HNO 3 and HNO 3 /H 2 SO 4 for 30 min. The band at 1454 cm −1 in the spectrum of the untreated fibres is attributed to CH 2 /CH 3 bending vibrations 25, 29, 33. Upon oxidation in acid, the appearance of the carbonyl/carboxy band at 1714 cm −1 is accompanied by an increase in intensity of the 1200 cm −1 absorption due to CO and OH groups.…”
Section: Resultsmentioning
confidence: 98%
“…All band assignments are summarised in Table 2, and all changes observed in the IR spectra after the different oxidative treatments are summarised in Table 3. The assignment of the bands of the untreated fibres is discussed elsewhere 25. The absorptions at 1633 and 1384 cm −1 are due to water and nitrate, respectively, adsorbed on the KBr and can be disregarded 19, 26–28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation